Effects of boundary conditions on a Bosch-type injection rate meter - Vass, Sandor; Zöldy, Máté (Transport, 2021)
Spread and evolution of Common Rail (CR) injection systems enable to influence injection events more efficiently than ever, while injection mass flow rate during an injection event crucially affects the combustion process. A measurement device based on the work of Bosch was set up, and measurements were made with different boundary conditions to explore the capabilities of the measurement system and to validate a detailed model of a CR injector. The main finding of this research work is, that orifice size had no noticeable effect on the measured injection rate traces, while it was stated in the original work that a small orifice is needed to terminate the measuring tube to maintain stable measurement conditions. Moreover, the backpressure level in the measuring system has a significant effect on the measured injection traces. If pressure in the measuring tube is low, gradient at the injection rate rise is lower, while if the pressure is comparable with that of a combustion chamber maximal compression pressure, measurement of higher doses is unaccomplishable due to the long pressure decrease time in the measuring tube after the end of the injection. Based on the results of the investigation, it can be stated that the Bosch-type injection rate measurement method does not give back the exact injection rate shape, a supplementing method would be necessary to calculate real nozzle flow rate.First published online 1 March 2021